2020
DOI: 10.1093/infdis/jiaa328
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus–Associated Myocardial Diastolic Dysfunction and Soluble ST2 Concentration in Tanzanian Adults: A Cross-Sectional Study

Abstract: Abstract Background The aims of this study were (1) to compare the prevalence of myocardial diastolic dysfunction (DD) in antiretroviral therapy (ART)–naive people living with human immunodeficiency virus (PLWH) to human immunodeficiency virus (HIV)–uninfected adults in East Africa and (2) to determine the association between serum concentration of the cardiac biomarkers ST2 and DD. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
9
1
Order By: Relevance
“…The majority of studies evaluating the prevalence of DD have been reported from developed countries where the prevalence of cardiovascular risk factors such as diabetes, hypertension, metabolic syndrome, IV drug use and mode of HIV infection are different 7 13. Studies in sub-Saharan Africa on the other hand have included symptomatic,38 hospitalised or untreated PLWH with advanced immune dysfunction 24 25. In our study of ART-treated PLWH with relatively normal CD4 +T cell counts, we specifically sought to enrol participants without known cardiovascular risk factors of diabetes or hypertension which promote DD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies evaluating the prevalence of DD have been reported from developed countries where the prevalence of cardiovascular risk factors such as diabetes, hypertension, metabolic syndrome, IV drug use and mode of HIV infection are different 7 13. Studies in sub-Saharan Africa on the other hand have included symptomatic,38 hospitalised or untreated PLWH with advanced immune dysfunction 24 25. In our study of ART-treated PLWH with relatively normal CD4 +T cell counts, we specifically sought to enrol participants without known cardiovascular risk factors of diabetes or hypertension which promote DD.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies linking HIV to DD have focused on PLWH with greater burden of comorbid conditions12 such as diabetes and hypertension,12 13 20 21 hepatitis C infection13 22 23 that confound the true association of DD with HIV infection. Similarly, the limited studies from Africa evaluating asymptomatic PLWH have included untreated cohorts24 25 or PLWH with high prevalence of cardiac comorbidities20 24 strongly associated with DD. The objective of this study was to characterise the prevalence of DD in ART treated PLWH in Kenya and a matched HIV-uninfected (HIV neg ) group, without known risk factors of diabetes and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies that evaluate associations between blood pressure control and LVH or LV dysfunction. Cross-sectional studies from Africa have found that people living with HIV have higher LV mass5 21 and higher rates of diastolic dysfunction9 21 even in the absence of hypertension and other cardiovascular risk factors, suggesting that HIV itself may independently contribute to increased LV mass and LV dysfunction 10 22. Proposed mechanisms for this include chronic inflammation and immune activation, even in the setting of viral suppression23–25 and increased pericardial fat density,21 which is common in people living with HIV and has been associated with coronary artery calcification and myocardial infarction 26–28.…”
Section: Discussionmentioning
confidence: 99%
“…HIV is associated with an increased risk for structural heart disease, including altered cardiac chamber size and volume4 5 and diastolic dysfunction 6 7. Changes in left ventricular (LV) mass and diastolic dysfunction have been described in studies of people living with HIV even when controlling for age, sex, ART and cardiovascular risk factors 8–10. Data on structural heart disease and associated risk factors in people living with HIV in sub-Saharan Africa remain limited as a result of poor availability of echocardiography, which has been challenging to provide as part of routine care due to lack of equipment and limited expertise to perform echocardiograms and interpret findings.…”
Section: Introductionmentioning
confidence: 99%
“…A sizeable cross-sectional Tanzanian study enrolled 388 antiretroviral therapy (ART) -naïve human immunodeficiency virus (HIV)- infected and 461 healthy adults to determine the association between serum sST2 levels and HIV-associated myocardial diastolic dysfunction, a known precursor of HFpEF [ 24 ]. The study revealed that HIV-infected adults had a higher prevalence of diastolic dysfunction (adjusted odds ratio [OR]: 2.71, 95% CI 1.62–4.55; p < 0.0001), and higher sST2 levels compared to the control group (19.6 vs. 16.1 ng/mL; p = 0.002).…”
Section: Biomarkersmentioning
confidence: 99%